IoT Phase Loss Monitoring System for Low Voltage Panels: Sistem Pemantauan Kehilangan Fase IoT untuk Panel Tegangan Rendah - Ananda Putra Suwarno; Syamsudduha Syahrorini Arifianto; Jamaaludin Suwarno (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Electrical distribution systems require reliable monitoring to prevent damage and service disruption caused by voltage anomalies. Specific Background Phase loss in low-voltage connection panels can lead to equipment damage and delayed handling due to conventional reporting systems. Knowledge Gap Existing complaint systems relying on SMS technology are inefficient and lack real-time monitoring capabilities. Aims This study aims to design and develop an Internet of Things-based phase loss monitoring and complaint system for low-voltage panels. Results The system utilizes NodeMCU ESP32, PZEM-004T sensors, GPS modules, and Telegram integration to monitor voltage conditions and send real-time notifications. Testing shows accurate voltage readings with an average accuracy of 98% and data transmission delay of 1.54 seconds. The system successfully detects abnormal voltage conditions below 220V, above 240V, and zero voltage while providing location information. Novelty The integration of real-time monitoring, automatic notification, and location tracking in a single IoT system provides a comprehensive solution for electrical disturbance handling. Implications This system supports faster response by technicians and improves operational efficiency in managing electrical distribution disturbances. Keywords: IoT Monitoring, Phase Loss, Low Voltage Panel, ESP32, PZEM-004T Key Findings Highlights Voltage anomaly detection operates with high measurement precision Notification delivery shows consistent low latency performance Location tracking enables rapid identification of disturbance points